Do high-altitude natives have enhanced exercise performance at altitude? - Brutsaert, T. D. (Applied Physiology, Nutrition, and Metabolism, 2008)
Abstract: Natives of high altitude (HA) may have enhanced physical work capacity in hypoxia due to growth and development at altitude or, in the case of indigenous Andean and Himalayan residents, due to population genetic factors that determine higher limits to exercise performance. There is a growing scientific literature in support of both hypotheses, although the specific developmental vs. genetic origins of putative population trait differences remain obscure. Considering whole-body measures of exercise performance, a review of the literature suggests that indigenous HA natives have higher mean maximal oxygen consumption (VO2 max) in hypoxia and smaller VO2 max decrement with increasing hypoxia. At present, there is insufficient information to conclude that HA natives have enhanced work economy or greater endurance capacity, although for the former a number of studies indicate that this may be the case for Tibetans. At the physiological level, supporting the hypothesis of enhanced pulmonary gas exchange efficiency, HA natives have smaller alveolar-arterial oxygen partial pressure difference ((A-a)DO2), lower pulmonary ventilation (VE), and likely higher arterial O2 saturation (SaO2) during exercise. At the muscle level, a handful of studies show no differences in fiber-type distributions, capillarity, oxidative enzymes, or the muscle response to training. At the metabolic level, a few studies suggest differences in lactate production/removal and (or) lactate buffering capacity, but more work is needed in this area.